THE PHENOMENON OF TRAMP AND THE AMERICAN SYSTEM OF SEPARATION OF POWERS - N. V. Molchakov; V. Y. Yakunin (Vestnik MGIMO-Universiteta)
The US political system is repeatedly subjected to significant deviations from those constitutional provisions that determine the relationship between the three branches of power. The scientists use such phrases as «Jacksonian democracy» or «Imperial presidency» to illustrate the attempts of American presidents to intervene those issues which constitutionally assigned to the other branches of power.  In general, despite these deviations from legally established rules, the elites retained a general consensus on the notion of stable domestic and foreign policies. As the main threat to this stability, the possibility of organizing a revolution from above was considered. However, in November 2016 D. Trump managed to be elected under the slogan of such a revolution, becoming the first the president in the political history of the United States, which has no firm support among the elites.  Undoubtedly, such a success illustrated serious problems within American society, that’s why the reasons of the conflict between D. Trump and his opponents could be found first of all in the ideological sphere. The newly elected president proposes a transformation of the fundamental basics that determined the vectors of US foreign and domestic policy in recent decades.  In this case, unlike the historical precedents considered in this paper, D. Trump’s criticism goes beyond simple accusations on the pages of the mass media or in statements of the leading representatives of the American political establishment. It takes a form of an acute confrontation between the branches of power and within them. The analysis of this situation is proposed in the article, both from the point of view of political and legal sciences, which could help to make a forecast on the chances of D. Trump to become a winner in this conflict within the American political elite.